(untitled) (Baghdad Science Journal, 2023)
In this work, functionally graded materials were synthesized by centrifugal technique at different volume fractions 0.5, 1, 1.5, and 2% Vf with a rotation speed of 1200 rpm and a constant rotation time, T = 6 min . The mechanical properties were characterized to study the graded and non-graded nanocomposites and the pure epoxy material. The mechanical tests showed that graded and non-graded added alumina (Al2O3) nanoparticles enhanced the effect more than pure epoxy. The maximum difference in impact strength occurred at (FGM), which was loaded from the rich side of the nano-alumina where the maximum value wasat 1% Vf by 133.33% of the sample epoxy side. The flexural strength and Young modulus of the functionally graded samples were enhanced by 43.69% and 52.74%, respectively, if loaded from the alumina-rich side. On the other hand, when loading (FGM) from the epoxy side, the amount of decrease in bending resistance was 122.4% while the improvement in bending modulus was 81.11% compared to pure epoxy. Scanning electron microscopy (SEM) revealed the fracture surface of the impact samples and the gradient scattering of nanoparticles in the epoxy matrix. Numerous applications can be used to manufacture the functionally graded material by centrifugal casting method, including for the manufacture of gears and all bending applications such as leaf springs.